1988
DOI: 10.1007/bf02390391
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of normal and pathological white matter maturation

Abstract: Fifty children between 3 months postnatal and 16 years of age were examined by means of a 1.5 T superconductive magnet, run at 0.35 and 1.0 T. The myelination was studied qualitatively and quantitatively (relaxation times, proton densities, image contrast). With increasing age, a decrease of T1 and proton density of white matter was found, which was complete at one year of age. In regions with a slow progression of myelination, gray/white matter contrast showed an increase up to the end of the first decade. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 8 publications
1
15
3
Order By: Relevance
“…It is wellknown that the developmental changes in water content of the brain affect the MR signal and that most water content of the brain reduces in the first year [12,21]. The T1 values decrease steadily during the first year for white and gray matter, with no changes after age 1 year [26]. Histologic studies of the brains of infants less than 12 months of age found that the increase in white matter intensity on T1-weighted images is explained by water decrease in the brain, not by myelination [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is wellknown that the developmental changes in water content of the brain affect the MR signal and that most water content of the brain reduces in the first year [12,21]. The T1 values decrease steadily during the first year for white and gray matter, with no changes after age 1 year [26]. Histologic studies of the brains of infants less than 12 months of age found that the increase in white matter intensity on T1-weighted images is explained by water decrease in the brain, not by myelination [15].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, myelination was examined by using MRI qualitative or semiquantitative ratings in normal infants and children [8,15,16,18,20,22,[27][28][29][30]36,38,39]. As many studies have shown that delayed myelination in children is related to developmental delay [13,14,16,31,40], it is important to establish the pace of myelination in normal children.…”
Section: Myelination Examination By Mrimentioning
confidence: 99%
“…As many studies have shown that delayed myelination in children is related to developmental delay [13,14,16,31,40], it is important to establish the pace of myelination in normal children.…”
Section: Myelination Examination By Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of finding abnormalities in myelination in relation to functional (neuro)development has been studied extensively. Correlation was found between neurodevelopmental delay and delay in myelination [53][54][55][56][57][58][59][60][61].…”
Section: Long-term Consequences Of Perinatal Brain Injurymentioning
confidence: 99%